Inducing early flowering in Andean cultivars adapted to low temperature - White, J.W.; Davis, J.H.C.; Castillo, J. (1987)
Five bean cv. were exposed to natural daylength (approx. 12 h) and ambient temp., or to 6 h daylength, achieved by moving pots into a darkened room to determine their response to photoperiod. Cv. Mortino and Frijolica 0- 3.2 did not flower under the control conditions, but with the short day treatment, they flowered in 40 and 41 days, resp. A subsequent expt. using 2, 4, 6, and 8 wk. treatments of the 6 h photoperiod was performed to test whether limited exposure to short days would result in adequate flowering. Adequate pod set was achieved using short days for the 1st 6 wk. Germplasm from highland areas can be induced to flower in 40 days by using 6 h days and a mean temp. of 24 degrees Celsius. (CIAT)